Extraction and Characterization of 7-Hydroxycoumarin from Pseudohandellia umbelliferae - Lari, Jalil; Vahedi, Hooshang; Hashemi, Zia (Asian Journal of Chemistry, 2010)
Pseudohandellia umbelliferae collected from Kalat Naderi area, Khorasan Razavi province, Iran was investigated and confirmed the presence of 7-hydroxycoumarin by spectroscopic methods.